Effect of Mineral and Chemical Admixture on Fiber Reinforced Self Compacting Concrete - Malya, S. Snigdha; A. Mounika, A. Mounika; C. Deepika, C. Deepika; Viswanath, V. Kasi; Keziya, N.; Basha, S. Hussain; Deepak, K. Lakshmi (Journal of Neonatal Surgery, 2025)
The objective of this work is to investigate the toughness property of the fiber reinforced self compacting concrete (FRSCC) through experimental studies. Fibers are used to arrest the cracks in the concrete, and also improve the toughness property of the concrete. In this work, different (0.5%, 1.0%, 1.5%, and 2%) percent of steel fibers are added by volume of concrete and (0.5% & 1.0%) percent of poly-propylene are added by mass of compendious material. The mix design of self-compacting concrete has been done according to the EFNARC guidelines. The limitations stipulated in European guidelines are also achieved according to the European guidelines. By using different types of fibers, the toughness property of the FRSCC has been studied. It has been observed that the toughness increased with increase in % of fibers up to 1.5%. While, increase in % fiber content beyond 1.5% resulted in lower toughness for the steel fibers. It gives a conclusion that the only the limitation of steel fiber for SCC is up to 1.5% of volume of concrete. The comparative study also recorded mechanical properties of poly- propylene fiber reinforced self-compacting concrete